Transcript Abundance Patterns of 9- and 13-Lipoxygenase Subfamily Gene Members in Response to Abiotic Stresses (Heat, Cold, Drought or Salt) in Tomato (Solanum lycopersicum L.) Highlights Member-Specific Dynamics Relevant to Each Stress - Upadhyay, Rakesh K. (Genes (Basel), 2019)
Lipoxygenases (LOXs; EC 1.13.11.12) catalyze the oxygenation of fatty acids to produce oxylipins including the jasmonate family of plant hormones. The involvement of jasmonates in plant growth and development and during abiotic stress has been documented, however, the response and regulation of each member of the LOX gene family under various abiotic stresses is yet to be fully deciphered. Previously, we identified fourteen members of the tomato LOX gene family, which were divisible into nine genes representing the 9-LOX family members and five others representing the 13-LOX family members based on the carbon oxidation position specificity of polyunsaturated fatty acids. Here, we have determined the transcript abundance patterns of all the 14 LOX genes in response to four independent abiotic stresses, namely, heat, cold, drought and salt. Our results show that each of these stresses leads to a time-dependent, variable or indifferent response of specific and different set(s) of LOX gene members of both subfamilies, differentiating functional relevance of the 14 LOX genes analyzed. Out of the 14 gene members, three LOX genes were expressed constitutively or were non-responsive to either heat (SlLOX9), cold (SlLOX9) or salt (SlLOX4) stress. An in-silico LOX gene promoter search for stress-responsive elements revealed that only some but not all of the LOX genes indeed are decorated with specific and known stress responsive cis-acting elements. Thus, these data implicate some other, yet to be discovered, cis-acting elements present in the LOX gene family members, which seemingly regulate tomato responses to defined abiotic stresses presented here.